THE IMPLEMENTATION OF MUDHARABAH FINANCING RISK MANAGEMENT IN THE SHARIA FINANCIAL SERVICES COOPERATIVE (CASE STUDY ON AL ABRAR SHARIA FINANCIAL SERVICES COOPERATIVE) - Ady Wena Pramudya; Puji Sucia Sukmaningrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to analyze the implementation of Mudharabah Financing in the Al Abrar Islamic Financial Services Cooperative in the city of Surabaya. Sharia financial services cooperatives require a series of procedures and methodologies that can be used to identify, assess, mitigate and evaluate risks arising from Mudharabah financing. This study uses a qualitative approach with case study research methods. The technique of collecting data uses direct interviews, documentation and observation. Purposive techniques are used in determining the unit of analysis. The analysis technique used is narrative-descriptive analysis, which describes the results of interviews and direct observation. Then to find out the validity of the data, researchers used triangulation techniques by matching the findings of primary data and secondary data. The results of this study indicate that Al Abrar Surabaya Islamic Financial Services Cooperative processes the risk management at the stage of identification, assessment, mitigation and risk control. This can be indicated through the way the Al Abrar Financial Services Cooperative deals with customers who fail to pay.Keywords: Risk Management, Risk, Customers, Islamic Financial Services CooperativesREFFERENCEAntonio, M. S. (2001). Islamic banking (bank syariah dari teori ke praktik). Jakarta: Gema Insani.Idroes, F. N. (2008). Manajemen risiko perbankan pemahaman pendekatan pilar kesepakatan basel. Jakarta: PT. RajaGrafindo Persada.Karim, A. A. (2010). Bank islam: analisis fiqh dan keuangan. Jakarta: PT. Raja Grafindo Persada.Rivai, V., & Andriapermata, V. (2008). Islamic financial management: teori, konsep, dan aplikasi (panduan praktis untuk lembaga keuangan, nasabah, praktisi, dan mahasiswa). Jakarta: PT Raja Grafindo.Mirakhor, Abbas, & Iqbal, Z. (2008). Pengantar keuangan islam: teori dan praktik. Jakarta: Kencana Prenada Media Grup.nawawi, i. (2009). Ekonomi kelembagaan Syariah. Surabaya: Putra media nusantara.Ronny, K. (2008). Mudah memahami manajemen resiko perusahaan. Jakarta: PT. Salemba Empat Patria.Siahaan, H. (2007). Manajemen risiko: konsep, kasus & implementasi. Jakarta: PT. Elex Media KomputindoSugiyono. (2012). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: AlfabetaYin, R. (2006). Studi kasus: desain & metode. Jakarta: PT RajaGrafindo Persada.